Experimental evaluation of PMMA simulated tunnel stability under dynamic disturbance using digital image correlation. (October 2019) - Tang, Zhili; Yao, Wei; Zhang, Junchen; Xu, Qianjun; Xia, Kaiwen
Highlights: The tunnel stability under dynamic disturbance is experimentally investigated. The influence of lateral pressure coefficient on failure feature is not monotonic. The effects of overbreak and underbreak and fault on failure pattern are studied. The damage of the tunnel varies with the direction of the dynamic disturbance. The digital image correlation method can characterize the evolution of deformation. Abstract: The dynamic disturbance is a non-ignorable external factor inducing rock mass instability around underground caverns. In this paper, the failure characteristics of the polymethylmethacrylate (PMMA) simulated tunnel under coupled biaxial static stress and high strain rate dynamic disturbance are experimentally investigated. The effects of lateral pressure coefficient, overbreak and underbreak, fault, and dynamic disturbance direction on the PMMA simulated tunnel failure are considered. During the tests, the two-dimensional digital image correlation (DIC) technique is used to monitor the failure process. The results indicate that the contribution of the dynamic disturbance on the failure of the PMMA simulated tunnel is closely related to the static in-situ stress. Sufficient static stress is essential for PMMA simulated tunnel failure under dynamic disturbance. The effect of the lateral pressure coefficient is not monotonic but depends on the relationship between horizontal and vertical in-situ stresses. For specimens with prefabricated defects, the cracks always initiate from the protruding defects with rough boundary. Thus, in areas where the tunnel is seriously under-excavated or over-excavated with rough boundary, attention should be taken to prevent and mitigate the severe damage caused by dynamic disturbances. The effect of the fault on the PMMA simulated tunnel stability depends on both the distance between the fault and the tunnel, and the dip of the fault. Most devastating failure occurred when the dynamic disturbance is applied in the direction of the higher static in-situ stress.